The Effect of Dayak Onion Bulb-Stem (Eleutherine Palmifolia (L.,) Merr.) Extract on Blood Glucose Levels of Mouse Suffered Diabetes Mellitus - Arwati, Niluh; Wijatmadi, Bambang; Adriani, Merryana; Meilanani, Soenarnatalina; Winarni, Dwi; Hartiningsih, Sri (Health Notions, 2018)
Dayak onions (Eleutherine Palmifolia (L.) Merr.) bulb stem contains phtyochemical contents, which act as antidiabetic compounds, such as eleutherol, eleuthocide A, and eleutherinoside B, as well as antioxidant compounds, which include triterpenoid, poliphenol, and flavonoid. Dayak onions was able to be used as the antidiabetic, since it had the ability to lower the blood glucose level and prevent from the free radicals, thus supressing the oxidative stress condition. This research had purpose to analyze the effect of Dayak onions bulb-stem as antioxidant and anti diabetic drugs. The research used experimental method with the population in this research was 25 male white mice strain wistar. The concentration of Dayak onions bulb-stem extracts were 300mg.kgBW-1, 400mg.kgBW-1, and 500mg.kgBW-1. Data analysis used Tukey HSD Test with 95% of  significance degree and was continued using manova test (average group ratio test). The result showed that. the extract of Dayak onions bulb-stem had the antidiabetical and antioxidant activity, which could lower the blood glucose levels and malondialdehid on the male white mice strain Wistar with the optimum effective doze of 500 mg.kgBW-1.   Keywords: Dayak onions bulb-stem, Blood glucose level, Malondialdehid (MDA)